Planerski in urbanistični projekti - neavtorski pristop in vprašanje sinergije pri sodelovanju - Jankovič, Liljana (Urbani izziv, 2005)
The article presents the non-author approach to urbanistic and planning projects. The project leader guides the entire project team, yet particular coordinators are also important. Contrary to authorship in architectural projects, in physical planning authorship is often or even always completely shared. Not only because planning projects can change significantly during adoption procedures, but mainly because there are many participating actors (designers, planners, commissioners and/or investors etc.) that are involved in any project''s undertaking. Experience proves that the non-author approach is beneficial for good project management and creation of conditions for constructive cooperation within an interdisciplinary working group and with all the other contributing parties. Two tested examples are presented. Their comparison is very interesting, since the first example shows a project where good cooperation between the client, investor and designers, as well as willing interested public, conditioned quality improvements, while the second (because of the public and consequently against its interests) diminished its quality significantly. Our judgement is that the quantity of the often mentioned necessity of public involvement is actually sufficient. There are noobstacles for public participation in urbanistic and physical planning, as long as the public is interested. Troubles are often triggered elsewhere - howto safeguard the common, public interest before particular publics (e.g. neighbours, the immediately affected etc.).
Keywords: javnost; prostorski razvoj; prostorsko planiranje; spatial planning; urbanism; urbanizem